Marginal Fit of Metal-Ceramic Copings: Effect of Luting Cements and Tooth Preparation Design - Santos Paes de Almeida, Juliana Gomes dos; Guedes, Carlos Gramani; Abi-Rached, Filipe de Oliveira [UNESP]; Trindade, Flavia Zardo [UNESP]; Fonseca, Renata Garcia [UNESP] (Wiley-Blackwell, 2019)
Purpose To evaluate the effect of the triad finish line design, axial wall convergence angle, and luting cement on the marginal fit of metal copings used in metal-ceramic crowns. Materials and Methods Schematic dies and their respective copings were cast in NiCr alloy. The dies exhibited the following finish line/convergence angle combinations: sloping shoulder/6 degrees, sloping shoulder/20 degrees, shoulder/6 degrees, shoulder/20 degrees. Marginal fit was evaluated under a stereomicroscope, before and after cementation. Copings were air-abraded with 50 mu m Al2O3 particles and cemented with Cimento de Zinco, RelyX U100, or Panavia F cements (n = 10/group). Data were square-root transformed and analyzed by 3-way factorial random effect model and Tukey's post hoc test (alpha = 0.05). Results Statistical analysis showed significance for the interactions finish line and convergence angle (p < 0.05), convergence angle and time (p < 0.001), and luting cement and time (p < 0.001). Sloping shoulder/20 degrees provided the highest marginal discrepancy when compared to the other finish line/convergence angle combinations, which were statistically similar among each other. For both convergence angles and for all luting cements, the marginal discrepancy was significantly higher after cementation. Before and after cementation, 6 degrees provided better marginal fit than 20 degrees. After cementation, Panavia F provided higher marginal discrepancy than Cimento de Zinco. Conclusion Lower convergence angle combined with shoulder and a low-consistency luting cement is preferable to cement metal copings.
Keywords: Axial-wall convergence angle; finish line design; luting cement; marginal fit; nickel-chromium alloy